PENGARUH KEPERCAYAAN PADA PEMERINTAH, MORALITAS PERPAJAKAN DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN PAJAK UMKM DI KOTA BATAM - Vincent Yang; Risca Azmiana (SCIENTIA JOURNAL, 2025)
This study was conducted to determine the factors that influence Tax Compliance among MSMEs in Batam City. These factors include Trust in Government, Tax Morality, and Tax Socialization. This study used a quantitative approach, with primary data obtained using questionnaires. The research population consists of MSMEs located in Lubuk Baja District and Bengkong District, totaling 237, with a sample size of 149 MSMEs, determined using the Slovin formula with a 5% error rate. This study employs Probability Sampling techniques using Random Sampling methods. The research methods include Descriptive Analysis, Instrument Testing, Classical Assumption Testing, Multiple Linear Regression Testing, and Hypothesis Testing, which were conducted using SPSS version 25. The research findings conclude that Trust in the Government, Tax Morality, and Tax Socialization simultaneously have a significant impact on MSMEs Tax Compliance in Batam City. Among these, Trust in the Government and Tax Morality significantly influence MSMEs Tax Compliance in Batam City. Meanwhile, Tax Socialization does not significantly influence MSMEs Tax Compliance in Batam City. It is concluded that H1 is accepted, H2 is accepted, H3 is rejected, and H4 is accepted.